Research on Simulation Analysis Method of Microbial Cemented Sand Based on Discrete Element Method - Yang Tang; Guobin Xu; Jijian Lian; Yue Yan; Dengfeng Fu; Weichen Sun (Advances in Materials Science and Engineering)
A simulation method for microbial cemented sand (MCS) based on the Two-Dimensional Particle Flow Code (PFC 2D) has been developed in this study. It consists of an identification of mesoscopic contact model for structural mesoscopic particles, development of morphological algorithm for irregular crystal particles, and classification and setting of mesoscopic parameters for compositional materials and particle size distribution simulation. Additionally, an acoustic emission algorithm based on moment tensor theory was developed for discrete element simulation analysis on fracture characteristic of cemented sand under the action of the force. The simulation method proposed in this article/paper may reflect the physical and mechanical characteristics of real microbial cemented sand based on physical experiments. Quantification of the fracture process of microbial cemented sand is possible by introducing a moment magnitude (MW) in discrete element simulation analysis. The material may have greater probability of fracture between the MW ranges of −6.8 and −6.6. The relationship between probability of fracture at different MWs and the MW follows the Gaussian curve. The research results are a new trial for fracture analysis on microbial cemented sand.